Influence of rapid weight reduction on physical ability in wrestling competition focusing on revision rules - Yabiku, S.; Kobayashi, T.; Seki, S.; Matsumoto, S.; Hwang, I. (The Journal of Physical Fitness and Sports Medicine, 2018)
[Aims] In the wrestling competition, the weighing rules were revised from 2018, and the weighing will be carried out two hours before each of the two days game. In this research, we decided to compare physical ability before and after rapid weight reduction using weight loss and weighing system assuming game. [Method] The subjects were 8 males at the university including wage national competition winning levels. Weight reduction was made twice, 5% and 10% of the body weight of each subject, respectively, and a rapid weight reduction of 7 days assuming game was carried out. In addition, a recovery period of 3 weeks was inserted between two reductions. Body composition, grip strength, back strength, side step, standing jump, rope climbing, maximum pedaling for 30 seconds, respectively, are given before weight reduction (Pre), 1 day after weight loss (Post 1) and 2 days after weight loss (Post 2) it was measured. [Results] There was a significant decrease in body weight, body water content and fat free mass in Post 1 and Post2 compared with Pre (p<0.05), there were no significant differences in the other items. [Conclusion] It was suggested that the body°s ability did not decrease with a rapid weight loss of 5% of body weight. Currently in progress at 10% weight loss, we will report on the day of the conference.